Pockets of risk in European housing markets: then and now - Jane Kelly; Julia Le Blanc; Reamonn Lydon (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
Using household survey data, we document evidence of a loosening of credit standards in Euro area countries that experienced a property price boom-and-bust cycle. Borrowers in these countries exhibited significantly higher loan-to-value (LTV) and loan-to-income (LTI) ratios in the run up to the financial crisis, and an increasing tendency towards longer-term loans compared to borrowers in other countries. In recent years, despite the long period of historically low interest rates and substantial house price increases in some countries, we do not find similar credit easing as before the crisis. Instead, we find evidence of a considerable change in borrower characteristics since 2010: new borrowers are older and have higher incomes than before the crisis.
Keywords: E5; G01; G17; G28; R39; 330; real estate markets; macroprudential policy; systemic risk; financial crises; bubbles; financial regulation; financial stability indicators